2018
DOI: 10.1080/15374416.2018.1485105
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of ADHD Symptoms in Toddlers

Abstract: The purpose of this study is to examine the psychometric properties of the 18 Diagnostic and Statistical Manual of Mental Disorders (DSM) symptoms of attention deficit/hyperactivity disorder (ADHD) in 2-year-old children. ADHD is typically diagnosed in elementary school, but research suggests that many children with ADHD first show symptoms during the toddler years. An important first step in identifying toddlers who are at high risk for developing ADHD is to better understand the properties of DSM symptoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The occurrence of each symptom was rated on a 4-point scale for the past 6 months (0 = never or rarely, 1 = sometimes, 2 = often, and 3 = very often). Many studies support the reliability and validity of scores from these parent and teacher rating scales with children from the United States (e.g., Barkley & Murphy, 2005;Brown & Harvey, 2019;DuPaul et al, 1997;Molina et al, 2001; as well as other countries including Spain (e.g., Burns et al, 2013;Marín-Méndez, Borra-Ruiz, Álvarez-Gómez, McGoey, & Soutullo, 2019;Servera & Cardo, 2007;Servera, Lorenzo-Seva, Cardo, Rodríguez-Fornells, & Burns, 2010;Vallejo-Valdivielso, Soutullo, de Castro-Manglano, Marin-Mendez, & Diez-Suarez, 2017). Given the ADHD and ODD symptoms did not change from DSM-IV-TR to DSM-5, the symptoms on the current scales also apply to DSM-5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of each symptom was rated on a 4-point scale for the past 6 months (0 = never or rarely, 1 = sometimes, 2 = often, and 3 = very often). Many studies support the reliability and validity of scores from these parent and teacher rating scales with children from the United States (e.g., Barkley & Murphy, 2005;Brown & Harvey, 2019;DuPaul et al, 1997;Molina et al, 2001; as well as other countries including Spain (e.g., Burns et al, 2013;Marín-Méndez, Borra-Ruiz, Álvarez-Gómez, McGoey, & Soutullo, 2019;Servera & Cardo, 2007;Servera, Lorenzo-Seva, Cardo, Rodríguez-Fornells, & Burns, 2010;Vallejo-Valdivielso, Soutullo, de Castro-Manglano, Marin-Mendez, & Diez-Suarez, 2017). Given the ADHD and ODD symptoms did not change from DSM-IV-TR to DSM-5, the symptoms on the current scales also apply to DSM-5.…”
Section: Methodsmentioning
confidence: 99%
“…One possibility is that the ADHD-IN, ADHD-HI, and ODD factors may not be as distinguishable with young children or organized in a different manner (e.g., Beauchaine, Zisner, & Sauder, 2017; Martel, Levinson, Smith, & Lee, 2017; McDonough-Caplan & Beauchaine, 2018; Willoughby, Blanton, & Family Life Project Investigators, 2015). Brown and Harvey (2019), for example, reported a correlation of .94 between the ADHD-IN and ADHD-HI factors from a CFA with toddlers. Such a high correlation would argue against separate ADHD-IN and ADHD-HI factors for toddlers even though the two-factor model fit better than the one-factor model.…”
Section: Objectives Of Studymentioning
confidence: 99%
“…For most children who later develop ADHD disorder, behaviors of inattention and hyperactivity/impulsivity start to emerge during the preschool years (DuPaul et al, 2001; Halperin et al, 2012). The behavioral characteristics of ADHD are similar in preschool and school age children (Brown & Harvey, 2019). Nonetheless, some studies have shown that during preschool age years, behaviors of ADHD are infrequent and often lack stability (Curchack-Lichtin et al, 2014), while others have shown that these behaviors are quite common in preschool children (Smidts & Oosterlaan, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] However, recent work looking at DSM-5 symptoms of ADHD in conjunction with temperament has demonstrated that children with ADHD show early behavioral signs of developmental delay during the preschool years. [6,7] Such children often have parents with the disorder. For example, work linking genetics, heritability, and familial risk of ADHD has found that parents with ADHD are 50-80% more likely than parents without ADHD to have one or more children with the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of ADHD typically occurs once children are in school and experience disruption to their academic and social lives [4, 5]. However, recent work looking at DSM-5 symptoms of ADHD in conjunction with temperament has demonstrated that children with ADHD show early behavioral signs of developmental delay during the preschool years [6, 7]. Such children often have parents with the disorder.…”
Section: Introductionmentioning
confidence: 99%